2014
DOI: 10.1093/gbe/evu030
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vertebrate Roots for Mammalian Zinc Finger Transcription Factor Subfamilies

Abstract: While many vertebrate transcription factor (TF) families are conserved, the C2H2 zinc finger (ZNF) family stands out as a notable exception. In particular, novel ZNF gene types have arisen, duplicated, and diverged independently throughout evolution to yield many lineage-specific TF genes. This evolutionary dynamic not only raises many intriguing questions but also severely complicates identification of those ZNF genes that remain functionally conserved. To address this problem, we searched for vertebrate “DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 61 publications
5
95
0
Order By: Relevance
“…Third, KAP1 deletion in neuronal progenitors activates some endogenous retroelements (Fasching et al, 2015), and selected ERVs are similarly induced in murine B lymphocytes or mouse embryonic fibroblasts (MEFs) depleted for SETDB1 (Collins et al, 2015;Wolf et al, 2015b). Correspondingly, human KRAB-ZFPs display extensive and cell-specific patterns of expression in all adult tissues examined Liu et al, 2014). Furthermore, the mouse-specific KRAB-ZFPs ZFP932 and Gm15446 are also involved in controlling their TE targets in somatic tissues, where they modulate the TE-mediated regulation of neighboring genes in vivo (Ecco et al, 2016).…”
Section: Heterochromatin Induction In Early Development and Te Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…Third, KAP1 deletion in neuronal progenitors activates some endogenous retroelements (Fasching et al, 2015), and selected ERVs are similarly induced in murine B lymphocytes or mouse embryonic fibroblasts (MEFs) depleted for SETDB1 (Collins et al, 2015;Wolf et al, 2015b). Correspondingly, human KRAB-ZFPs display extensive and cell-specific patterns of expression in all adult tissues examined Liu et al, 2014). Furthermore, the mouse-specific KRAB-ZFPs ZFP932 and Gm15446 are also involved in controlling their TE targets in somatic tissues, where they modulate the TE-mediated regulation of neighboring genes in vivo (Ecco et al, 2016).…”
Section: Heterochromatin Induction In Early Development and Te Controlmentioning
confidence: 99%
“…Studies in human and mouse showed that KAP1 depletion in these cells leads to differentiation and metabolic defects (Santoni de Sio et al, 2012a,,b;Chikuma et al, 2012). The KRAB-ZFPs responsible for these phenotypes, however, have not yet been identified, but many are specifically expressed in these tissues (Liu et al, 2014;Imbeault et al, 2017). Other events influenced by KRAB-ZFPs include osteogenesis (Jheon et al, 2001), mammary gland development (Oliver et al, 2012) and the formation of extra-embryonic tissues .…”
Section: Krab-zfps In Cell Differentiationmentioning
confidence: 99%
See 3 more Smart Citations